The impact of peri-natal stress on psychosis risk: results from the Bo-FEP incidence study - De Matteis, Tiziano (BMC Res Notes, 2020)
OBJECTIVE: According to the gene-environment interaction model the pathogenesis of psychosis relies on an adverse neuro-socio-developmental pathway. Perinatal stress represents an important risk factor for the development of psychosis because of the increasingly evident interference with socio-neuro-development in the earlier phases of life. We aim to investigate the correlation of perinatal risk factors with the onset of psychosis with a case–control–incidence study. RESULTS: Patients (and their mothers) were eligible if they presented with first-episode psychosis at the Bologna West Community Mental Health Centre (Bo-West CMHC) between 2002 and 2012. The Bo-West CMHC serves a catchment area of about 200,000 people. The controls were recruited in the same catchment area and study period. 42 patients, 26 controls and their mothers were included. We collected the history of peri-natal stress and calculated crude and adjusted Odds Ratios for onset of first-episode psychosis. Adjusted logistic regression showed that psychosis onset was significantly associated with stressful situations during pregnancy, lower level of maternal physical health before or during pregnancy, use of anti-inflammatory drugs during pregnancy, and low level of maternal education. The results of our study suggest that stress during perinatal period increases the risk of developing psychosis.